1977
DOI: 10.1149/1.2133504
|View full text |Cite
|
Sign up to set email alerts
|

Electrons in Liquid Ammonia

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
181
0
5

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(193 citation statements)
references
References 0 publications
5
181
0
5
Order By: Relevance
“…give estimates for average 17 O and 1 H hfcc constants that are comparable to the averages obtained using more diffuse basis sets (Table 4S). Isotropic hfcc's for protons are small ( a H < 1 G): either slightly negative or slightly positive (Table 3S).…”
supporting
confidence: 62%
See 3 more Smart Citations
“…give estimates for average 17 O and 1 H hfcc constants that are comparable to the averages obtained using more diffuse basis sets (Table 4S). Isotropic hfcc's for protons are small ( a H < 1 G): either slightly negative or slightly positive (Table 3S).…”
supporting
confidence: 62%
“…suggesting that EPR results of Schlick et al 30 for 17 O substituted glasses (used to justify the one-electron models) were compromised, as was also suggested by subsequent studies by the same authors (section 2). 49 While the one-electron point-dipole octahedral ("Kevan's") model 24 While the magnetic parameters for different trapping sites show considerable variation, the mean values are similar to the ones obtained in simple cluster models provided that the mean cavity size is the same.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…8 In fact, there is indirect experimental evidence for the formation of bound pairs of electrons in solutions of metals dissolved in liquid ammonia; the metal/ammonia solutions show a decrease in magnetic susceptibility at high concentrations of excess electrons, suggesting that the electrons' spins become paired. 9 Mixed quantum/classical density functional calculations also have suggested that bound pairs of electrons form at high electron densities in liquid ammonia. 10 In water, simulations have shown 11 that hydrated dielectrons occupy a larger, less spherical cavity than (single) hydrated electrons.…”
Section: Introductionmentioning
confidence: 99%